DEVELOPMENT OF FAIRY TALE CALENDAR MEDIA TO TRAIN THE SPEAKING SKILLS OF GRADE III STUDENTS OF ELEMENTARY SCHOOL 104303 KAMPUNG IBUS SERDANG BEDAGAI SCHOOL YEAR 2023/2024 - Nurhafizoh, Nurhafizoh; Hidayat, Wahyu; Ramadhani, Mastari (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2024)
This research aims to develop a fairy tale calendar media with material about loving plants and animals for students. to determine the level of appropriateness of media use and determine the level of practicality of the media through student responses, after using fairy tale calendar media. This research uses the Research and Development (R&D) research method with the ADDIE research model which has five stages (analysis, design, development, implementation and evaluation. The data collection technique used is: validation of material expert questionnaires and media expert questionnaires to determine the level of feasibility media as well as a response questionnaire from educators and students to determine the level of practicality of the media. The subjects of the research and development were class III students at SD Negeri 104303 Kampung Ibus, Sei Rampah District. The results of the research and development obtained a design in the form of a fairy tale calendar media to train the speaking skills of class III students at SD Negeri 104303 Kampung Ibus which received an appropriateness score of 88.57% by media experts, 98.66% by material experts. Based on the results of the description above, the product developed by the researcher is suitable and practical for use as a learning medium.